2020
DOI: 10.2337/db19-1034
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pancreatic Blood Flow: Bidirectional Microcirculation Between Endocrine and Exocrine Pancreas

Abstract: The pancreatic islet is a highly vascularized endocrine micro-organ. The unique architecture of rodent islets, a so-called core-mantle arrangement seen in two-dimensional images, led researchers to seek functional implications for islet hormone secretion. Three models of islet blood flow were previously proposed, all based on the assumption that islet microcirculation occurs in an enclosed structure. Recent electrophysiological and molecular biological studies using isolated islets also presumed unidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
(53 reference statements)
1
53
0
1
Order By: Relevance
“…Here we show that changes in the activity of islet pericytes and “SMC” pericytes mediate vasomotion in human islets and propose that these cells function as local gates. Given recent functional evidence in mice that the islet microcirculation is open and not isolated from that of the surrounding exocrine tissue ( 51 ), and the fact that in humans an islet-portal circulatory system is also well developed ( 41 ), the existence of such a gating system would allow islet blood flow to be regulated independently of the exocrine tissue under certain conditions, as previously suggested ( 52 ).…”
Section: Discussionmentioning
confidence: 91%
“…Here we show that changes in the activity of islet pericytes and “SMC” pericytes mediate vasomotion in human islets and propose that these cells function as local gates. Given recent functional evidence in mice that the islet microcirculation is open and not isolated from that of the surrounding exocrine tissue ( 51 ), and the fact that in humans an islet-portal circulatory system is also well developed ( 41 ), the existence of such a gating system would allow islet blood flow to be regulated independently of the exocrine tissue under certain conditions, as previously suggested ( 52 ).…”
Section: Discussionmentioning
confidence: 91%
“…These studies suggested that a paracrine effect of glucagon on pancreatic beta cells in rodents is probably relatively minor. This view of rodent islet blood flow has long been under discussion (see [39] for the different models of islet microcirculation) and new observations utilising in vivo imaging of islet blood flow challenge even these models [40], making the issue of paracrine effects through the bloodstream for rodent islets open for debate. Another study arguing against the importance of a paracrine interaction between alpha and beta cells involved the generation of the glucagon-DTR mouse, a mouse that expressed the diphtheria toxin receptor (DTR) in pancreatic alpha cells.…”
Section: Is Glucagon a Paracrine Signal In Vivo?mentioning
confidence: 99%
“…Islets, comprised of highly vascularised clusters of endocrine cells, are the functional units within the pancreas that control blood sugar levels. A dense capillary network surrounds and penetrates each pancreatic islet to enable glucose sensing and insulin secretion into peripheral circulation ( 5 8 ). While representing only 1–2% of the pancreatic mass, islets receive up to 20% of the direct arterial blood flow to the pancreas ( 9 ).…”
Section: Introductionmentioning
confidence: 99%